2012
DOI: 10.1002/btpr.1659
|View full text |Cite
|
Sign up to set email alerts
|

Solubility properties and diffusional extraction behavior of natamycin from streptomyces gilvosporeus biomass

Abstract: Natamycin is a type of polyene macrolide antibiotic and has been produced in submerged microbial cultures of some natural Streptomyces strains. Natamycin extraction from cellular biomass is greatly affected by the molecular and solubilization characteristics of the extraction solvent, and this is a major reason for the routine attainment of low volumetric titers, resulting from sparing natamycin solubility. In this work, a series of experiments were conducted to investigate the solubility of natamycin in some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…It can be seen from Figure that the absorbance increased by increasing natamycin concentration up to 100 mg/L above which a plateau is obtained for solutions after centrifugation (10,000 × g; 15 min). Regarding the isoelectric point of natamycin (6.5), it is expected that aggregation and particle collision can occur at pH 7.0 close to its pI due to the abatement of the molecular mutual force which resulted in reduction of its solubility (Zeng et al, ) as confirmed by increasing absorbance for solutions before centrifugation for concentrations above the threshold. Based on the results achieved for the solubility of natamycin in buffer at neutral pH, the concentration of 45 mg/L was selected for studying its antifungal activity incorporated in CAS/LMP composite films.…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen from Figure that the absorbance increased by increasing natamycin concentration up to 100 mg/L above which a plateau is obtained for solutions after centrifugation (10,000 × g; 15 min). Regarding the isoelectric point of natamycin (6.5), it is expected that aggregation and particle collision can occur at pH 7.0 close to its pI due to the abatement of the molecular mutual force which resulted in reduction of its solubility (Zeng et al, ) as confirmed by increasing absorbance for solutions before centrifugation for concentrations above the threshold. Based on the results achieved for the solubility of natamycin in buffer at neutral pH, the concentration of 45 mg/L was selected for studying its antifungal activity incorporated in CAS/LMP composite films.…”
Section: Resultsmentioning
confidence: 99%
“…Because natamycin is insoluble in water, the washing ability of water is poor; in contrast, natamycin is soluble in methanol and acetonitrile, making the washing abilities of methanol and acetonitrile much better. Therefore, a methanol and acetonitrile mixture was chose to use as the drip washing solution (Zeng et al, 2013;Zheng et al, 2009). A series of methanol acetonitrile mixtures were used (methanol proportions of 20%, 30%, 40%, 50%, 60%, 70%, and 80%) and the result is shown in Fig.…”
Section: Optimization Of the Spe Conditionsmentioning
confidence: 99%